(untitled) (Italian Review of Legal History, 2017)
Trying to answer to the question if is it possible to apropriate the European legal legacy for writing a decolonialized history of international law and if is this task possible also for a european legal historian, this article aims to rethink the attitude of international lawyers to identify the international law as a scientific and systematic discipline. Focusing on the works of Carl Schmitt it intends to reconnect the international law and the colonial discourse revealing the ambiguous relationships between two different stories that seemed for too long time to be different and doomed to run in parallel without ever meeting.